Evaluation of automated anaerobic fermentation processes as in the case of mould infected maize - Bíró, Györgyi; Mézes, Lili; Borbély, János; Tamás, János (Acta Agraria Debreceniensis, 2013)
In Hungary the renewable energy utilization is planned to achieve 13% by 2020. Biogas production is one of the fields with the largest energy potential. Achieving high efficiency during continuous production despite the mixed and variable composition of input materials is the most common problem which the newly built biogas plants using agricultural raw materials have to deal with. The first experimental reactors at the Department of Water and Environmental Management were built 12 years ago. Control and automation of the four separated bioreactors were executed with ADVANTECH GENIE 3.0 software which granted pre-programmed measurement and points of intervention for pH, temperature, CH4, CO2, H2S, and NH3. The system became out-of-data, therefore in 2010 it has been redesigned and tested. The system is controlled by Compair Proview SCADA (Supervisory Control and Data Acquisition) software running on Linux platforms. The Fusarium infection caused serious yield-losses in cereal production in 2010. In the case of cereal products, which non-utilizable as forage seems an optimal solution is utilizing as biogas raw material. The raw material was based on the Fusarium infected maize. In the recent publication infotechnological and technological experiences of the pilot test period are evaluated as well as direction of future development is defined.